Surgical Precision in Thyroid Management: Advancements in Techniques and Postoperative Care - Johar Iqbal, Fazal Rehman, Saeed Khan, Muhammad Arif, Allah Noor, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To evaluate the outcomes of conventional thyroidectomy in patients undergoing surgery at tertiary care hospital, and to assess the impact of comorbidities on postoperative complications and recovery. Methodology: A retrospective analysis was conducted on 120 patients who underwent conventional thyroidectomy between June 2021 and June 2022. Data were collected from medical records, including patient demographics, comorbidities, postoperative complications, and the length of hospital stay. Descriptive statistics were used to summarise the data, and a chi-squared test was applied to assess associations between comorbidities and complications, with a significance level set at p < 0.05. Results: The mean age of the patients was 42.5 years (SD = 14.7), and the mean hospital stay was 3.83 days (SD = 2.15). The most common comorbidities were Cardiovascular disease (29 patients, 30.9%), Hypertension (24 patients, 25.5%), and Diabetes (23 patients, 24.5%). The most frequent postoperative complications included Postoperative bleeding (29 patients, 32.6%), Recurrent laryngeal nerve injury (22 patients, 24.7%), and Wound infection (19 patients, 21.3%). The chi-squared test revealed a significant association between comorbidities and complications (p = 0.003). Conclusion: The study emphasises the role of comorbidities in increasing the risk of complications following thyroidectomy. Targeted preoperative assessment and management of patients with underlying health conditions can reduce complication rates and improve recovery. Larger, multicenter prospective studies are recommended to validate these findings. Keywords: Thyroidectomy, Postoperative Complications, Comorbidities, Recovery, Hypocalcaemia.